2010
DOI: 10.2165/11537790-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guanfacine Extended Release on Oppositional Symptoms in Children Aged 6–12 Years with Attention-Deficit Hyperactivity Disorder and Oppositional Symptoms

Abstract: NCT00367835.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
81
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 52 publications
8
81
0
2
Order By: Relevance
“…A post-hoc analysis from that study reported a positive correlation (r = 0.74) between reductions in CPRS-R:L oppositional scores and ADHD-RS-IV scores (Connor et al 2010). This is consistent with a meta-analysis of three placebo-controlled studies of atomoxetine in children and adolescents with ADHD, which showed correlations of similar magnitude between changes in oppositional and ADHD symptoms .…”
supporting
confidence: 81%
See 2 more Smart Citations
“…A post-hoc analysis from that study reported a positive correlation (r = 0.74) between reductions in CPRS-R:L oppositional scores and ADHD-RS-IV scores (Connor et al 2010). This is consistent with a meta-analysis of three placebo-controlled studies of atomoxetine in children and adolescents with ADHD, which showed correlations of similar magnitude between changes in oppositional and ADHD symptoms .…”
supporting
confidence: 81%
“…A more recent double-blind, placebo-controlled monotherapy study examined treatment with GXR in children with ADHD and the presence of significant oppositional symptoms (Connor et al 2010). In this study, the presence of significant oppositional symptoms was defined as a baseline Conners' Parent Rating ScaleRevised: Long Form (CPRS-R:L) oppositional subscale score ‡ 14 (for boys) or ‡ 12 (for girls).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, doses above 54,55 as well as adjunctive pharmacotherapy in combination with stimulants for those patients who failed to have an adequate response with the latter medication. 26,50 All the different studies but one relied on changes on changes from baseline in the Attention-Deficit/ Hyperactivity Disorder Rating Scale IV (ADHD-RS-IV) as the primary outcome measure, with one exception 53 that used the ADHD-RS-IV as secondary outcome measure. Other secondary measures in the different reports included the BeforeSchool Functioning Questionnaire, Conners Global IndexParent, Conners Parent Rating Scale -revised: short form (CPRS-R:SF), CPRS-R: long form (CPRS-R:LF), Conners Teacher Rating Scale -revised, Clinical Global Impressionimprovement (CGI-I), CGI -severity, Parent Global Assessment (PGA), and Child Health Questionnaire -parent form.…”
Section: Dosage and Administrationmentioning
confidence: 99%
“…57 Data from 143 children with ADHD (6-12 years of age) taking GXR from the 9-week RCT evaluating the effects of GXR on comorbid oppositional symptoms 53 were compared with the data from a subset analysis of 98 children aged 7-13 years taking ATX from two identical, 9-week, multisite, doubleblind RCTs assessing the safety and efficacy of ATX in ADHD and comorbid ODD. 58 GXR was associated with a significantly greater reduction in mean CPRS-R:LF oppositional subscale scores compared with ATX (-5.0 versus -2.4, ES 0.58; P=0.01).…”
mentioning
confidence: 99%